Pengaruh website quality terhadap user perceived value (studi empiris pada e-commerce tokopedia) - Punang Amaripuja; Affiana Aulia (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to determine the effect of website quality on user perceived value on one of the e-commerce in Indonesia. This study is a quantitative study with Tokopedia e-commerce as the object, the sample obtained in this study amounted to 143 respondents whose data will later be processed using SPSS 29. The results of this study indicate that usability, information quality, service interaction quality, and website quality have a significant positive influence on user perceived value. While for open questions, the results are that the majority of respondents said that Tokopedia has good performance and has a good website. This study consists of 3 independent variables and 1 dependent variable where the website quality variable consists of 3 independent variables, namely usability, information quality, and service interaction quality. Based on the researcher's direct experience in this research process, the Tokopedia website must maintain and improve the services provided to users. This is because users have experienced good service when transacting on the Tokopedia website and the Tokopedia website must maintain and improve the appearance of the website. This is because users have had a positive experience with the appearance of the Tokopedia website. This study used Google Forms to collect data, but it was not possible to ask follow-up questions to clarify the answers. The open-ended questions presented a weakness in the respondents' responses. Furthermore, the open-ended questions presented difficulties in processing because the answers were difficult to classify.